Review of respiratory physiotherapy methods in patients with cystic fibrosis - Oktawia Kuna; Katarzyna Stachura; Paweł Niemiec (Śląski Uniwersytet Medyczny w Katowicach, 2023)
Respiratory physiotherapy is an integral part of the therapy of patients with cystic fibrosis. Patients should be rehabilitated regularly and systematically throughout their lives, and should become independent in pulmonary rehabilitation as soon as possible. Knowledge of the methods and principles of pulmonary rehabilitation by physiotherapists will allow the proper selection of respiratory physiotherapy techniques. The aim of the study was to compare pulmonary rehabilitation methods used in cystic fibrosis patients from birth to adolescence. To achieve the goal, two authors searched the following databases: PubMed, the Cochrane Library and Google Scholar from June 2021 to December 2021. 58 articles were included in the review. There are few studies confirming the effectiveness of one method over the other, and the discrepancies in the methodology of source works prevent unequivocal conclusions. The selection of techniques should be appropriate to the needs of patients with cystic fibrosis. For this purpose, physiotherapists should broaden their knowledge of the methods of pulmonary rehabilitation confirmed by both practical skills and scientific evidence.